Comparison of Rugae Pattern Between Dentate and Edentulous Patients in Iraqi Sample - Inas A Jawad (University of Mosul, College of Dentistry, 2010)
Aim: To explore the volatile topographic changes occurring in the palatal rugae after aging and loss of all teeth. Materials and methods: The total sample consists of 40 Iraqi participants in 2 , dentate and edentulous , groups. Their maxillary casts were minutely observed. Number, lengths, qualitative cha-racteristics, and medial position of the rugae ends were recorded. Results: Many differences were ob-served between the 2 groups. Conclusions: Palatal rugae were topographically changed greatly after aging and loss of teeth regardless of time of edentulism and wearing dentures. Short , simple , scattered and anteriorly flared is the overall picture of rugae in edentulous palates .